The current development status of training and education for anesthesia specialty nurses (麻醉专科护士培训教育及发展现状) - JI Jing (季静); MA Yanli (马燕利) (中西医结合护理)
This paper summarizes the research progress of training and education of anesthesia specialist nurses at home and abroad, sorts out the training objects, training contents and training methods, and discusses the consensus points and existing problems in the clinical training of anesthesia specialist nurses that have been carried out in China. Reference were provided for clinical hospitals to establish and standardize the training system of anesthesia specialist nurses. (本研究概述国内外麻醉专科护士培训教育的研究进展, 对培训方式及培训内容等方面进行归纳梳理, 讨论麻醉专科护士临床培训中的共识点及存在的问题, 以期为院校建立和规范完善的麻醉专科护士培训体系提供参考依据。)